Thoracic bilateral sympathectomy attenuates oxidative stress and prevents ventricular remodelling in experimental pulmonary hypertension. (27th December 2021) - Coutinho e Silva, Raphael dos Santos; Wiggenhauser, Lucas Moritz; Simas, Rafael; Zanoni, Fernando Luiz; Medeiros, Geisla; da Silva, Fernanda Beatriz; Ogata, Daniel Cury; Breithaupt-Faloppa, Ana Cristina; Krenning, Guido; Moreira, Luiz Felipe Pinho
Abstract: OBJECTIVES: Pulmonary arterial hypertension (PAH) is a cardiopulmonary disease that affects the pulmonary vasculature, leading to increased afterload and eventually right ventricular (RV) remodelling and failure. Bilateral sympathectomy (BS) has shown promising results in dampening cardiac remodelling and dysfunction in several heart failure models. In the present study, we investigated whether BS reduces pulmonary arterial remodelling and mitigates RV remodelling and failure. METHODS: PAH was induced in male Wistar rats by intraperitoneal injection of monocrotaline. Rats were divided into 3 groups, involving untreated PAH ( n  = 15), BS-treated PAH ( n  = 13) and non-manipulated control rats ( n  = 13). Three weeks after PAH induction, the rats were anaesthetized and RV function was assessed via the pressure-volume loop catheter approach. Upon completion of the experiment, the lungs and heart were harvested for further analyses. RESULTS: BS was found to prevent pulmonary artery remodelling, with a clear reduction in α-smooth muscle actin and endothelin-1 expression. RV end-systolic pressure was reduced in the BS group, and preload recruitable stroke work was preserved. BS, therefore, mitigated RV remodelling and cardiomyocyte hypertrophy and diminished oxidative stress. CONCLUSIONS: We showed that thoracic BS may be an important treatment option for PAH patients. Blockade of the sympathetic pathway can prevent pulmonary remodelling and protect the RV from oxidative stress, myocardial remodelling and function decay. Abstract : Pulmonary arterial hypertension (PAH) is a cardiopulmonary disease that affects both the pulmonary vasculature and the right ventricle (RV).